Barriers to Disclose HIV Status to Family Members Among People Living with HIV - Ibrahim, Kusman; Rahayuwati, Laili; Herliani, Yusshy Kurnia (Jurnal Keperawatan Soedirman, 2019)
Disclosing HIV status has inhibited HIV infected persons from getting access to sufficient prevention, care, treatment, and support, which in turn can contribute to poor HIV/AIDS control. This study aims to explore the reasons underlying the barriers to disclosing HIV status to family members among people with HIV infection. This is a qualitative exploratory study. Forty participants participated in the study which was divided into five focus group discussions. They were purposively recruited from two district hospitals in West Java. FGDs were audiotape recorded with permission from participants and were verbatim transcribed. Data were analyzed qualitatively by thematic analysis technique. Four major themes emerged from the data; 1) Negative feelings about being a HIV-infected person, 2) Feeling fear of being rejected by family members, 3) Avoiding being a burden on the family, 4) Desiring to maintain a good relationship with family members. The study suggested that nurses and health care providers need to consider family as the primary source of support and encouragement for people with HIV infection. Strengthening the self-confidence of PLWH and family coping strategies needs to be more emphasized when caring for people with HIV infection particularly in the first stage after being diagnosed as HIV positive.